2018
DOI: 10.1371/journal.pone.0192574
|View full text |Cite|
|
Sign up to set email alerts
|

Post-discharge body weight and neurodevelopmental outcomes among very low birth weight infants in Taiwan: A nationwide cohort study

Abstract: BackgroundPremature infants are at high risk for developmental delay and cognitive dysfunction. Besides medical conditions, growth restriction is regarded as an important risk factor for cognitive and neurodevelopmental dysfunction throughout childhood and adolescence and even into adulthood. In this study, we analyzed the relationship between post-discharge body weight and psychomotor development using a nationwide dataset.Materials and methodsThis was a nationwide cohort study conducted in Taiwan. Total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 69 publications
1
27
0
1
Order By: Relevance
“…Meanwhile, other examples of aforementioned neurological conditions showed very similar prevalence in the NPC and PC groups in both the NICU and the well-baby nursery. Though seemingly counterintuitive, this pattern is consistent with previous studies that show development of these pathologies is strongly correlated with the infant's gestational age [21] [24], which is especially pertinent in the NICU cohort, and whose distribution was similar between NPC and PC groups. However, as mentioned earlier, this might imply that seeking and completing prenatal care appropriately can benefit the mother-infant dyad by lowering the maternal risks associated with pregnancy, potentially increasing the birth weight of the infant and lowering the risk for developing pulmonary complications [25] [26] Open Access Library Journal [27].…”
Section: Conclusion For Practicesupporting
confidence: 90%
See 2 more Smart Citations
“…Meanwhile, other examples of aforementioned neurological conditions showed very similar prevalence in the NPC and PC groups in both the NICU and the well-baby nursery. Though seemingly counterintuitive, this pattern is consistent with previous studies that show development of these pathologies is strongly correlated with the infant's gestational age [21] [24], which is especially pertinent in the NICU cohort, and whose distribution was similar between NPC and PC groups. However, as mentioned earlier, this might imply that seeking and completing prenatal care appropriately can benefit the mother-infant dyad by lowering the maternal risks associated with pregnancy, potentially increasing the birth weight of the infant and lowering the risk for developing pulmonary complications [25] [26] Open Access Library Journal [27].…”
Section: Conclusion For Practicesupporting
confidence: 90%
“…Also notable was that birth weights were lower in the NPC group in both the NICU and newborn nursery, causing them to be more susceptible to medical complications. Also, the NPC group in the NICU showed a longer duration of respiratory support, a factor that contributed to a longer NICU stay (25.7 days in NPC group; 24.5 days in PC group) and chronic pulmonary conditions requiring further medical attention later in life [21]. When these chronic pulmonary conditions co-occur with low birth weight, they can significantly compromise the health of children later on in life.…”
Section: Conclusion For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…20 Hsu et al also found that SGA was a significant factor for postdischarge failure to thrive in another nationwide cohort study in Taiwan. 14 Since postdischarge GR correlated to poorer neurodevelopmental outcomes, it is important to give adequate nutrition support for catch-up growth in SGA VLBW infants. 14 However, postnatal rapid weight gain in SGA infants seemed to be associated with increased fat mass and cardiovascular disease in later life.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, the growth of VLBW infants may be affected by perinatal, cultural, ethnic, or environmental factors. 5,8,10,13,14,16 The present study described the prevalence of postdischarge GR among VLBW infants in Taiwan and identified possible risk factors for postdischarge GR from nationwide registry data.…”
Section: Introductionmentioning
confidence: 94%